Raymunida Macpherson & Machordom, 2000 (Crustacea: Decapoda: Anomura: Munididae) from the KUMEJIMA 2009 Expedition in the Ryukyu Islands, Japan - Osawa, Masayuki (Zootaxa, 2012)
Two species of the munidid genus Raymunida Macpherson & Machordom, 2000, are reported from Kume Island, RyukyuIslands, southwestern Japan. Raymunida striata n. sp. appears closest to R. confundens Macpherson & Machordom, 2001,and R. dextralis Macpherson & Machordom, 2001, but is distinguished by the second and third abdominal somites eachwith an uninterrupted stria between two distinct transverse ridges on the dorsal surface, the merus of the third maxillipedwith a prominent distal spine on the extensor margin, and the mero-carpal articulation of the fourth pereopod reachingonly to the lateral end of the anterior cervical groove of the carapace. The occurrence of R. vittata Macpherson, 2009, inKume Island greatly extends its distribution range to the north hemisphere. Morphological variations of R. vittata are also discussed on the basis of the present specimens. An updated key to the species of Raymunida is provided.